Prevención de Oídium sp, en el cultivo de tomate riñón (Lycopersicum esculentum Mill), mediante el uso de Bacillus subtilis sector de San Joaquín, cantón Bolívar, Provincia del Carchi - Escobar Manrique, Marco Vinicio (2018)
VII SUMMARY. The present investigation was carried out in the San Joaquín Sector of the Bolívar parish of the Bolívar province of the Carchi province, located at geographic coordinates of 0 ° 31`16 "north latitude and 77 ° 55'54.4" west longitude, with a altitude of 2980 masl. The theoretical methods were used: Inductive-deductive, synthesis analysis and the empirical one called experimental. The Design of Completely Random Blocks (DBCA) was applied, with a factorial arrangement (A X B) +1, specific treatments were included plus an absolute witness giving a total of 7 treatments and three repetitions. The objectives set in the evaluation were; evaluate the incidence of Oídium sp, in tomato kidney culture, by applying Bacillus subtilis in three doses (high, medium and low), determine the efficiency of the best application dose, establish the most effective application system in the prevention of the disease and perform the economic analysis of the treatments. It was obtained as results; (factor A) Fertirrigation application systems showed higher averages in stem diameter, presented lower incidence and severity of the disease, likewise it was evidenced the highest yield per experimental unit, in the application doses the High obtained greater diameter of stem, lower incidence and severity of the disease and higher yield, the treatment (Fertirrigation in high dose 2cc / L of water) record significant averages in the evaluation of; stem diameter, in the incidence and severity of the disease lower percentage, greater yield within the area of the experimental unit and the highest economic profitability was $ 34,978.25 USD / ha.